Understanding the link between older volunteers' resources and motivation to volunteer. Issue 2 (1st February 2016) - Principi, Andrea; Schippers, Joop; Naegele, Gerd; Di Rosa, Mirko; Lamura, Giovanni
ABSTRACT: The purpose of this study was to investigate the impact of older volunteers' available human, social, and cultural capital on their motivational forces to volunteer, measured through the Volunteer Function Inventory. A large European database of 955 older volunteers (i.e., aged 50+) was employed, and Seemingly Unrelated Regressions showed that older volunteers have different motivations according to different sets of individual resources. Furthermore, lower amounts of human and social capital (e.g., low educational level, poor health, being widowed, divorced or single) are associated with a higher propensity to volunteer to enhance one's own self-esteem, to avoid thinking of personal problems, and for social reasons. These results have important implications for policy makers and voluntary organizations if they want to enhance volunteering among older people with less resources, i.e., that are more at risk of social exclusion. For example, according to the results of this study, policy makers could consider developing more tailored opportunities for involving older volunteers with low educational level, poor health, widowed, divorced, or single. They could do this by underlying that volunteering offers possibilities to satisfy motivational needs important to the, elderly, e.g., to increase self-esteem, to deal with personal problems in a better way, and to have satisfying social contacts.